2021
DOI: 10.1007/s00247-021-05018-7
|View full text |Cite
|
Sign up to set email alerts
|

Magnetic resonance imaging for congenital lung malformations

Abstract: Congenital lung malformations are most often identified on prenatal US screening. Fetal MRI is often performed to further evaluate these lesions. Although some of these lesions might cause prenatal or early postnatal symptoms that require urgent management, the majority are asymptomatic at birth and might be subtle or invisible on chest radiographs. Postnatal imaging is frequently deferred until 3–6 months of age, when surgery or long-term conservative management is contemplated. High-quality imaging and inter… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
11
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 13 publications
(11 citation statements)
references
References 30 publications
0
11
0
Order By: Relevance
“…Other investigators have also observed that cystic PPB may be indistinguishable from CPAM by CT. 20 , 21 , 22 , 36 Although magnetic resonance imaging may play a diagnostic role in a few cases, this imaging modality usually provides suboptimal visualization of the lung parenchyma owing to low magnetic resonance signal from proton-poor lung tissue. 37 …”
Section: Discussionmentioning
confidence: 99%
“…Other investigators have also observed that cystic PPB may be indistinguishable from CPAM by CT. 20 , 21 , 22 , 36 Although magnetic resonance imaging may play a diagnostic role in a few cases, this imaging modality usually provides suboptimal visualization of the lung parenchyma owing to low magnetic resonance signal from proton-poor lung tissue. 37 …”
Section: Discussionmentioning
confidence: 99%
“…They can cause severe respiratory distress and admission to the neonatal intensive care unit (ICU) [68]. Congenital lung malformations (CLM) can be prenatally diagnosed with US screening, eventually complemented with antenatal MRI for a more accurate evaluation [69]. They are usually discovered during the mid-second-trimester US (19-22 weeks of pregnancy) with well-defined sonographic patterns to assess location, size, composition (solid, cystic or mixed), and blood supply.…”
Section: Congenital Lung Malformationsmentioning
confidence: 99%
“…Congenital lung malformations, including congenital pulmonary airway malformation (CPAM), extra- and intralobar bronchopulmonary sequestration, congenital lobar and segmental emphysema, and bronchogenic cyst, are amongst the most frequent abnormalities detected in utero [ 1 , 2 ]. With improved prenatal ultrasound, the incidence has seen a rise; however, congenital lung malformations remain a rare condition in the overall population [ 3 , 4 ].To date, the management of congenital lung malformations, such as CPAM, bronchopulmonary sequestration and the overlap of these two (hybrid lesions), is still controversial. For children symptomatic at birth, a surgical approach, such as lobectomy, segmentectomy or cyst removal, is widely accepted [ 5 , 6 ].…”
Section: Introductionmentioning
confidence: 99%